Structural change, social inclusion, and environmental sustainability: New perspectives and policies in economic development - Isabella, Fernando; Castillo, Jimena; Yajima, Giuliano Toshiro (PSL Quarterly Review, 2024)
This special issue addresses the challenges of the international economy, focusing on structural change, social inclusion, and environmental sustainability. It brings together contributions from senior and young scholars, many from Latin America, to explore multidimensional issues like inequality, geopolitical tensions, financial instability, environmental crises, and technological asymmetries. The selected papers, initially presented at the 1st International Workshop on Structural Change, Social Inclusion, and Environmental Sustainability, provide diverse perspectives on topics such as economic policy for a fair transition, centre-periphery dynamics, and the intersection of gender, labour, and economic growth. These works aim to foster collaboration between experienced and emerging voices, enriching the conversation around economic development through pluralist approaches.